Faktor-faktor yang Mempengaruhi Stres Kerja Karyawan Produsen Perhiasan - Padmawati, Ni Luh Listu Ayu; Kusyana, Dewa Nyoman Benni (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study was to determine the effect of interpersonal conflict, workload, and communication on employee work stress. This research was conducted at PT. Bonafactum which is located in Kerobokan Kelod Village. The population in this study were all employees, totaling 404 people. Sampling was determined using the Slovin Formula and a total of 80 people were determined using random sampling technique. The questionnaire was measured using a Likert scale. The instrument test was carried out by testing the validity and reliability of 30 respondents. The analysis technique used is multiple linear regression with SPSS software. The results of the determination test prove that the contribution of interpersonal conflict, workload, and communication to employee work stress is 79.9 percent. The results of the partial significance test prove interpersonal conflict, and workload have a positive and significant effect on work stress, while communication has a negative and significant effect on work stress.